Analysis of the Development Strategy of Urban Investment Companies Under the Perspective of Financial Generosity - Huang, Xiqi; Feng, Jing (Journal of Global Economy, Business and Finance, 2024)
This paper analyzes the current situation of the city investment company in terms of capital, funds and operation from the perspective of financial prosperity, based on the huge financing scale and potential risk situation of the city investment company, and takes A County City Investment Company as an example, and provides a new development mode and direction for the revitalization of the economy of the city investment company. From the perspective of "financial prosperity", it provides a new development mode and direction for revitalizing the economy of city investment company, and puts forward corresponding development strategies from the aspects of asset management, capital management and operation management.